Exporting and endogenous workplace amenities under monopsonistic competition - Avtandil Abashishvili (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
This paper introduces endogenous workplace quality choice into an international trade model with a monopsonistically competitive labour market, in which firms compete for potential employees by offering them a combination of monetary and non-monetary benefits. To attract the workers required to produce for the foreign market in addition to the domestic market, exporting firms have to offer more attractive compensation to their employees than comparable non-exporting firms, which is why they are not only paying higher wages but also offering better workplace amenities. The gains from trade, therefore, not only materialise in terms of a higher purchasing power but also in terms of a higher average workplace quality. Welfare metrics, which exclusively focus on real income gains, might underestimate the gains from globalisation. – – Dieser Beitrag endogenisiert die Wahl der Arbeitsplatzqualität in einem Außenhandelsmodell mit monopsonistischem Arbeitsmarkt. Unternehmen konkurrieren um potenzielle Mitarbeiter, indem sie ihnen eine Kombination aus monetären und nicht-monetären Vorteilen anbieten. Exportierende Unternehmen müssten eine attraktivere Entlohnung anbieten als vergleichbare nicht-exportierende Unternehmen, um Arbeitnehmer anzuziehen, die nötig sind, um zusätzlich zu dem inländischen Markt für den ausländischen zu produzieren. Deshalb zahlen sie nicht nur höhere Löhne, sondern bieten weitere nicht-monetären Zusatzleistungen an. Die Gewinne aus dem Handel kommen also nicht nur in Form einer höheren Kaufkraft zum Tragen, sondern auch in Form einer höheren durchschnittlichen Arbeitsplatzqualität. Wohlfahrtsindikatoren, die sich ausschließlich auf reale Einkommenszuwächse konzentrieren, könnten die Vorteile der Globalisierung unterschätzen.
Keywords: F12; F16; F23; 330; Monopsonistic competition; workplace quality; wages; exporting; gains from trade